(untitled) (Al-Academy, 2024)
The poster is one of the important media in the communication process, as it effectively contributes to spreading the necessary awareness and building a community culture that views health phenomena in society as topics that must be coexisted with naturally. In turn, we participate in addressing this phenomenon and reducing it by designing posters for student age groups. To deal with this phenomenon in a humane way that differs from bullying, so the researcher raised the following question to express the problem of her research: What is the iconic expression in the designs of posters for the phenomenon of bullying? The current research aims to reveal the iconic expression in the designs of posters for the phenomenon of bullying. The researcher adopted the descriptive approach in analyzing the models because it is a method of analysis that focuses on sufficient information about a particular phenomenon or topic within a specific period of time and then interprets it in an objective manner to reach acceptable generalizations in harmony with the actual data of the phenomenon, as the current research community includes international educational posters issued by UNICEF International participated in the International Day Against Violence and Bullying on (November 1, 2022), which the researcher collected in (10) posters in line with the research topic. The investigation produced a number of results, the most important of which are: The representation of cultural symbols in the poster gave its own cultural characteristic in achieving the design message that was reflected in the sample form No. (1). The employment of cultural symbols inspired by the cultural factors reflected in the poster design was achieved in the sample model (1,2). The most important conclusions are: The cultural factor is to enrich the design and express its content. The state of change in the environment of the cultural thought of society creates something similar in the poster. Culture is an extension of human minds and feelings and is a means of communication and transfer of information between the designer and the recipient in designing posters against the phenomenon of bullying. Keywords: expression - icon - bullying.